Nilai Akhlak Dalam Tradisi Mushofahah di Musholla Ahluls Kisa, Darul Musthofa Tarim, Yaman - Marjuki, Marjuki; Irfan, Ahmad (Universitas Muhammadiyah Tangerang, 2024)
The issue of moral crisis amidst the development of time, both personally and externally, becomes a significant concern for society as a whole. The tradition of mushofahah becomes an interesting phenomenon in the community at Musholla Ahlul Kisa Darul Musthofa Tarim, Yemen, in an effort to address moral issues. This research was conducted using a qualitative method with ethnographic research type. Primary data were obtained through interviews and observations, while secondary data were obtained through literature studies. The results of this study explain that there are three processes of mushofahah tradition, starting from before the dawn call to prayer and after the dawn prayer, as well as an interesting tradition of giving gifts to Habib Umar bin Hafidz. The values formed include moral values towards Allah, the Prophet, the Teacher, and social communities. The impact of the mushofahah tradition is the strengthening of family ties, building positive relationships between students and teachers, and eliminating seniority in the pesantren environment. Keywords: Mushofahah, Tradition, Morality, Tarim